Automação para aquisição de dados aplicada em processos de logística de uma montadora automobilística - Tortola, Bruno Henrique (2022)
This study aims to develop a tool to automatize the acquirement of data of two WMS - Warehouse Management Systems, utilized by an automotive company, which would speed not only the process of data acquirement, but also the confiability of the data acquired. The development was based on algorithms defined by simulating the manual usage flow, in which each step of the process of data acquirement was detailed; The final code was written in VBA language. Results show a monthly decrease of over a hundred hours of man work, distributed within the whole team, which is equivalent of approximately 12 thousand reais of man work hours that could be reallocated.